2021
DOI: 10.1016/j.sjbs.2020.09.058
|View full text |Cite
|
Sign up to set email alerts
|

Technical and economic potentials of the unconventional extruded dried Arabic bread wastes in broilers diets

Abstract: Food waste is one of the major global challenges that have adverse socioeconomic and environmental impacts. Therefore, studying food waste utilization potentials and minimizing its negative consequences becomes imperative. This study aims to assess the technical and economic potentials of substituting corn with unconventional extruded dried Arabic Bread waste (EDABW) in broilers’ diets, in terms of broilers’ performance, carcass characteristic, economic net returns, and income over feed cost (IOFC). One hundre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
3
1
1
Order By: Relevance
“…Scrutinization of Dried Bakery Waste as Maize Substitute in Quail Ration by Evaluating the Growth and Nutrient Utilization onwards; suggesting that raising meat quail birds after five weeks of age is uneconomical. Our results corroborates with the findings of different prior researchers who too reported similar findings in their respective studies (Edache et al, 2017;Epao et al, 2017;Al-Sagan et al, 2021;Lukanov et al, 2021). However, some authors reported results contradictory to that of the present study (Oke, 2013;Ayanrinde et al, 2014;Chauhan, 2021).…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Scrutinization of Dried Bakery Waste as Maize Substitute in Quail Ration by Evaluating the Growth and Nutrient Utilization onwards; suggesting that raising meat quail birds after five weeks of age is uneconomical. Our results corroborates with the findings of different prior researchers who too reported similar findings in their respective studies (Edache et al, 2017;Epao et al, 2017;Al-Sagan et al, 2021;Lukanov et al, 2021). However, some authors reported results contradictory to that of the present study (Oke, 2013;Ayanrinde et al, 2014;Chauhan, 2021).…”
Section: Resultssupporting
confidence: 90%
“…in BaW meal-fed treatment groups, it resulted in the comparable cost of starter feed, finisher feed as well as the total cost of feed. Noticeable reduction in the cost of total feed in broiler birds on increasing the levels of BaW inclusion as maize replacer was reported earlier by some researchers (Al-Ruqaie et al, 2011;Al-Sagan et al, 2021). Similar to our study, some authors reported a non-significant difference in the feed cost reduction per bird while using BaW as a maize replacer (Oke, 2013;Epao et al, 2017;Chauhan, 2021).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…According to the latter, the differences in the chemical composition of BM from 46 different regions of the USA are relatively small and are unlikely to have a major impact on their nutritional value. Previous reports have demonstrated that dietary BM can safely replace up to 50% of maize (when the main ingredients of the diet are maize and soya) in the diet of growing pigs and sows without any adverse effect on their health, yield, and carcass quality [28][29][30][31][32][33][34], while the integration of bakery by-products into animal feeds has also drawn attention in broiler and cow systems, demonstrating promising results [35][36][37].…”
Section: Introductionmentioning
confidence: 99%